От редактора - Bukh, Vladimir (проект байкал, 2006)
All-penetrating globalization reduces the neighborhood effect. Now we are all neighbors on the Earth. Nevertheless, to shake hands looking into each other's eyes remains an advantage of the tactile contact, which imparts to the parties a confidential frankness that is precious as it is. This metaphysics transfer to urban planning, architecture, people that are involved into it localizes our efforts but does not make them less fruitful and instructive. The instruction consists in leveling the levels like in communicating vessels. There is nothing more important for a steady neighborhood.